Analysis of the determinants that influence the time until diagnosis of clients with cancer (Research, Society and Development, 2023)
Objective: Since delays in diagnosis and/or treatment of cancer imply a lower chance of cure, worse prognosis and reduced survival, in addition to greater costs for clients, families and health systems, the objective is to determine the time in which cancer clients chemotherapy outpatient clinic of the Cancer Hospital I, of the National Cancer Institute, obtain a diagnosis, highlighting the impact of analyzed factors. Method: 105 clients were interviewed between March and August 2023 and multivariate regression analysis was used to examine the variables: diagnosis, age, sex, city of residence, color, family income, education, marital status, interval between onset from symptoms perceived by client until first healthcare service is sought and interval between first contact with healthcare service and the diagnosis. Results: An average time of 3 months was observed to seek care after the appearance of symptoms and factors that influenced time until the first consultation include education, color, marital status, city of origin and age. However, these variables did not show any influence on average time from consultation to diagnosis, which may be justified by the fact that after the client enters the health system, the difficulties (or ease) of access apply to everyone, regardless of their particularities and, in this case, the determinants act randomly. Final Considerations: Delays between initial symptoms and first consultation are associated with low education and lack of information about the disease. Delays between consultation and diagnosis are normally related to the care context.